Controlled mycorrhization of the endemic Chilean orchid Chloraea gavilu (Orchidaceae). (27th May 2021) - Pereira, Guillermo; Herrera, Héctor; Arriagada, César; Cid, Hertes; García, José Leonardo; Atala, Cristian
Abstract: Orchids require mycorrhizal fungi (OMF) for their germination and growth. Propagation and re-introduction initiatives would likely require inoculation with such fungi. All Chilean Orchidaceae species are terrestrial and likely associate with OMF. We collected adult individuals of the endemic Chilean orchid Chloraea gavilu and transported them to a glasshouse where we obtained mature capsules through manual auto-pollination. We asymbiotically germinated seeds in vitro using Malmgren Modified Terrestrial Orchid-Medium (MM). Embryos were put in glass flasks with MM where roots and leaves developed for 16 weeks. Plants were then transplanted to 165 mL pots and randomly separated into three groups; plants inoculated separately with Ceratobasidium OMFs isolated from two Chilean orchid species ( Chloraea virescens and Codonorchis lessonii ), and uninoculated (control) plants. Plants were then put in a growth chamber. Three months later, inoculated individuals showed pelotons inside parenchyma cells in the roots. Four months after inoculation, mycorrhizal plants had higher root and shoot biomass compared to control plants. At the end of the experiment, the highest mycorrhization was achieved with the Ceratobasidium strain isolated from C. lessonii . The artificial mycorrhization of endemic orchids could be a key strategy for future conservation and propagation initiatives, especially for endangered or commercially interesting species.